Diagnosis and treatment of Helicobacter pylori for peptic ulcer bleeding in clinical practice - factors associated with non-diagnosis and non-treatment, and diagnostic yield in various settings - Lim, Lee Guan; Ho, Khek Yu; So, Jimmy BY; Khor, Christopher JL; Lim, Li Lin; Teoh, Pui Li; Yeoh, Khay Guan (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To study the practice of clinicians in the diagnosis and treatment of H. pylori for peptic ulcer bleeding, and the diagnostic yield of H. pylori tests in various situations. Materials and Methods: All consecutive patients aged ≥18 years who underwent esophagogastroduodenoscopy for the indications of coffee-grounds vomitus, hematemesis or melena with endoscopically diagnosed peptic ulcers were included. Results: 374 patients were included. H. pylori testing was performed during acute bleeding for 296 patients. 80% of patients who tested negative for H. pylori during the acute episode were planned for repeat H. pylori testing. 11/88 patients who tested negative for H. pylori during the acute episode were positive for H. pylori during repeat testing (diagnostic yield 12.5%). Prior proton-pump inhibitor and antibiotic ingestion within 4 weeks of presentation was associated with lower diagnostic yield for H. pylori. On multivariate analysis, patient’s age, systolic blood pressure, heart rate, activated partial thromboplastin time, and need for endoscopic treatment were associated with failure to take biopsies for H. pylori testing during acute episode. 100/106 patients tested positive for H. pylori during the acute episode of gastrointestinal bleeding had H. pylori treatment. Conclusion: Repeat H. pylori testing after index negative H. pylori testing during acute episodes gave a diagnostic yield of 12.5%, reinforcing the importance of repeat testing.